Alzheimer`s Disease, Mild Cognitive Impairment and Mediterranean Diet. A Systematic Review and Dose-Response Meta-Analysis - García-Casares, Natalia; Gallego Fuentes, Paloma; Barbancho-Fernández, Miguel Ángel; López-Gigosos, Rosa María; García-Rodríguez, Antonio; Gutiérrez-Bedmar, Mario (MDPI, 2021)
Abstract: Alzheimer’s Disease (AD) is a pathology with increasing prevalence in the context of a more long-lived society and it is the first cause of dementia in western countries. It is important to investigate factors that can be protective and may influence its development, in order to act on them trying to reduce AD incidence and its progression. The aim of this study was to conduct a systematic review and meta-analysis to determine the effects of a higher adherence to Mediterranean diet (MD) on Mild Cognitive Impairment (MCI) and AD. A literature search in PubMed, The Cochrane Library Plus and Scopus was conducted, selecting articles that analyzed associations between MD adherence and AD biomarkers (Volumetry assessed by MRI and betamiloide and Tau deposits by PET); cognitive performance in patients at risk or presenting MCI and AD; and incidence or progression from MCI to AD. Out of the 589 studies screened, 22 studies met eligibility criteria for the systematic review and qualitative synthesis. Finally, 11 studies were included in the meta-analysis (12,458 participants). Higher adherence to MD was associated with a significantly lower risk of MCI (RR = 0.91, 95%CI = 0.85–0.97) and lower risk of AD (RR = 0.89, 95% CI = 0.84–0.93). Our results enhance the importance of taking health-promoting lifestyle measures like following Mediterranean dietary patterns in order to reduce AD risk.
Keywords: Alzheimer, Enfermedad de - Tratamiento; Mediterranean diet; Alhzeimer`s disease; Mild cognitive impairment; Meta-analyisis